Testing the scenario hypothesis: An experimental comparison of scenarios and forecasts for decision support in a complex decision environment. (May 2017) - Gong, Min; Lempert, Robert; Parker, Andrew; Mayer, Lauren A.; Fischbach, Jordan; Sisco, Matthew; Mao, Zhimin; Krantz, David H.; Kunreuther, Howard
Abstract: Decision support tools are known to influence and facilitate decisionmaking through the thoughtful construction of the decision environment. However, little research has empirically evaluated the effects of using scenarios and forecasts. In this research, we asked participants to recommend a fisheries management strategy that achieved multiple objectives in the face of significant uncertainty. A decision support tool with one of two conditions—Scenario or Forecast—encouraged participants to explore a large set of diversified decision options. We found that participants in the two conditions explored the options similarly, but chose differently. Participants in the Scenario Condition chose the strategies that performed well over the full range of uncertainties (robust strategies) significantly more frequently than did those in the Forecast Condition. This difference seems largely to be because participants in the Scenario Condition paid increased attention to worst-case futures. The results offer lessons for designing decision support tools.